2019
DOI: 10.1111/jfpp.14011
|View full text |Cite
|
Sign up to set email alerts
|

Effect of 1‐MCP on postharvest quality of French prune during storage at low temperature

Abstract: The effect of 1‐methylcyclopropene (1‐MCP) treatment on postharvest quality of French prune (Prunus domestica L.) during low temperature storage was investigated. French prunes were exposed to 1.2 μl/L 1‐MCP and stored at 1 ± 1°C under 90 ± 5% RH. The physiological and biochemical indexes were measured and recorded weekly throughout the experimental period. Our experimental results showed that 1‐MCP had a significant effect on maintaining fruit hardness (~20%), titratable acidity (~29%), ascorbic acid (~18%), … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 36 publications
0
4
0
Order By: Relevance
“…Tao et al (2017) Similarly, (Cao et al, 2015) found that treatment with 1-MCP at 1 μl/L delayed senescence and improved the quality of apricot fruit during storage at 0°C. Xiong et al (2019) reported that treatment with 1-MCP at 1.2 μl/L significantly inhibited the decrease in ascorbic acid content in French prune during storage at 1°C ± 1°C. But, in this study, no significant difference was found in ascorbic acid content between the untreated sample and the sample treated with 0.5 μl/L of 1-MCP.…”
Section: Effect Of 1-mcp Treatment On Titratable Acidity and Ascorbic Acidmentioning
confidence: 95%
“…Tao et al (2017) Similarly, (Cao et al, 2015) found that treatment with 1-MCP at 1 μl/L delayed senescence and improved the quality of apricot fruit during storage at 0°C. Xiong et al (2019) reported that treatment with 1-MCP at 1.2 μl/L significantly inhibited the decrease in ascorbic acid content in French prune during storage at 1°C ± 1°C. But, in this study, no significant difference was found in ascorbic acid content between the untreated sample and the sample treated with 0.5 μl/L of 1-MCP.…”
Section: Effect Of 1-mcp Treatment On Titratable Acidity and Ascorbic Acidmentioning
confidence: 95%
“…This fruit is highly perishable, as it ripens rapidly at ambient temperature, which drastically limits its storage life and marketing probability after harvest (Crisosto, Mitchell, & Ju, 1999). Low temperature storage is an effective way to slow down respiration and senescence process and to extend the postharvest life of plums (Xiong, Li, Liu, Li, & Gui, 2019). However, plum fruit suffer from chilling injury when stored at temperature between 0 and 5°C (Crisosto, Garner, Crisosto, & Bowerman, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…The present study revealed that all three treatments could effectively delay the decrease in ASA content, with the combined treatment having the best effect, possibly due to the fact that the secondary metabolism and antioxidant capacity of fruit was enhanced by UV-C. Ávila–Sosa et al [ 45 ] reported that pre-treatment of hawthorn with UV-C irradiation could maintain the ASA content during storage. In contrast, Xiong et al [ 40 ] indicated that ASA content in prune would be restrained by being treated with 1-MCP. Therefore, combining 1-MCP with UV-C treatment could be an efficient way to limit ASA degradation and promote the accumulation of total phenols and flavonoids in the ‘Xiaobai’ apricot fruit.…”
Section: Discussionmentioning
confidence: 97%
“…During the post-ripening of apricot fruit, 1-MCP could effectively restrain the increase in SSC and inhibit the decomposition of TA. Previous studies have revealed that 1-MCP treatment can effectively prolong the post-harvest ripening process of the French prune while hindering the increase in SSC [ 40 ]. Similarly, the rise of SSC and decreased TA was slower in combined treated apricot fruit, while the TA was higher in single-treatment groups.…”
Section: Discussionmentioning
confidence: 99%